Comparative Study of the Effects of Curcuminoids and Tetrahydrocurcuminoids on Melanogenesis: Role of the Methoxy Groups - Shilpi Goenka (Future Pharmacology, 2024)
Curcuminoids are naturally occurring yellow-colored compounds that, when hydrogenated to remove their conjugated double bond, become colorless and are referred to as tetrahydrocurcuminoids. Curcuminoids consist of pure curcumin (PC) in major amounts and demethoxycurcumin (DC) and bisdemethoxycurcumin (BDC) in minor amounts. Tetrahydrocurcuminoids similarly consist mainly of tetrahydrocurcumin (THC), along with minor amounts of tetrahydrodemethoxycurcumin (THDC) and tetrahydrobisdemethoxycurcumin (THBDC). Previous studies have shown the inhibitory effects of PC, DC, and BDC on melanin production, but there are contradictory findings about THC. In addition, there are currently no reports on the effects of THDC and THBDC on melanogenesis. Our previous report described that, in contrast to PC, which suppressed melanin production, THC stimulated melanin production in B16F10 and MNT-1 cells; this effect was ascribed to the loss of the conjugated heptadiene moiety of PC. However, whether this finding can be generalized to the two curcumin derivatives (DC and BDC), such that THDC and THBDC might also stimulate melanogenesis, has not been addressed. Herein, a comparative study of six curcumin derivatives (PC, DC, BDC, THC, THDC, and THBDC) was undertaken to identify their effects on melanogenesis with the goal of elucidating the structure–activity relationships (SARs) focused on assessing the two regions of the parent curcumins’ structure: (i) the hydrogenation of the two double bonds bridging the phenyl rings to the β-diketone moiety, and (ii) the effect of the ortho-methoxy substituent (-OCH3) on the two phenyl rings. To determine the direct effects of the six compounds, antioxidant activity and tyrosinase activity were assessed in cell-free systems before cellular experiments utilizing the B16F10 mouse melanoma cells, MNT-1 human melanoma cells, and primary cells. Evaluations were made on cytotoxicity, melanin concentration, and cellular tyrosinase activity. The results showed that BDC inhibited melanogenesis in B16F10 and MNT-1 cells. However, it was ineffective in primary human melanocytes, while THBDC continued to exhibit anti-melanogenic capacity in normal human melanocytes. Moreover, these findings provide a novel perspective into the role of the methoxy groups of PC on the biological effects of melanogenesis and also confirm that the removal of the conjugated double bonds abolishes the anti-melanogenic capacity of PC and DC only, but not BDC, as THBDC maintained anti-melanogenic activity that was greater than BDC. However, the outcome is contingent upon the specific kind of cell involved. To the best of our knowledge, this work presents novel findings indicating that the anti-melanogenic capacity of the colored BDC is not only intact but enhanced after its hydrogenation as observed in THBDC. The findings show potential for using colorless THBDC as a pharmacological candidate to diminish the increased pigmentation characteristic of skin hyperpigmentation disorders. Future pharmacological therapeutics that incorporate pure THBDC or THBDC-enriched extracts, which retain both a colorless appearance and potent anti-melanogenic activity, can be applied to compounds for anti-melanoma therapeutics where the demand for nontoxic novel molecules is desired for established efficacies.